E-GOVERNMENT: IMPLEMENTATION OF ASAN SERVICE MODEL FOR PUBLIC SERVICE REFORM IN NIGERIA AND SUDAN - Sodiya, Oluwaseyi Olubunmi; Elmahdi, Ali Ahmed Suliman (International Journal of Research -GRANTHAALAYAH, 2023)
Despite technological developments, customer acceptability is constrained due to a lack of functional knowledge. E-government growth ambitions do not include administrative simplification, lack of infrastructure and human resource capabilities, there is a mismatch between supply and demand for e-services. the Ineffective government regulations, scarcity of technical skills and exorbitant technological costs. Politicians, civil servants, and all public servants are seen as the actual enemy in these two countries, depriving them of progress and national development. This quantitative study proposed that the Azerbaijan ASAN service model be adopted as an alternative public services reform approach for reimagining Nigerian and Sudanese public services sectors. The findings indicate that Strongly Agree (n=3). Agree (N=21) contradicted disagreed (n=17) and strongly disagree (n=9). To summarize, n=25 respondents genuinely disagree that people in their country were aware of e-government services, which runs counter to (n=24). This result showed that almost everyone who participated in the survey agreed and recognized the value of using the Azerbaijan ASAN services model to make it easier for residents to receive government services in a corrupt-free digital environment. In conclusion, the adoption of e-Government services that are more advantageous, user-friendly, effective, and efficient may be significantly impacted by the study's findings, in our opinion. We recommend that the government to adopt and provide electronic services like ASAN service E-government of Azerbaijan.